Wages and reciprocity in the workplace - Barr, A; Serneels, P (2004)
We explore the role of reciprocity in wage determination by combining experimental and survey data. The experiment is similar to Berg, Dickhaut and McCabe's (1995) and is conducted with Ghanaian manufacturing workers. The survey relates to the same sample workers and the firms within which they are employed. We find a strong positive association between individual reciprocity and individual wages. However, the direction of causality is unclear. Various aspects of the distribution of the tendency to reciprocate within an employee's workforce are also associated with that employee's wage and, in this case, there are strong arguments for a causal link is from former to latter. In particular, the mean, median, and minimum levels of reciprocity have a positive effect on wages, while the spread in the distribution (standard deviation) has a strong significant negative effect. This suggests that homogenous behaviour, or convergence to a norm, is rewarded. The results underline the importance of behavioural characteristics and firm culture for the operation of the labour market.